2020
DOI: 10.1186/s12913-020-05904-0
|View full text |Cite
|
Sign up to set email alerts
|

A stoic and altruistic orientation towards their work: a qualitative study of healthcare professionals’ experiences of awaiting a COVID-19 test result

Abstract: Background Extensive measures to reduce person-to-person transmission of COVID-19 are required to control the current outbreak. Special attention is directed at healthcare professionals as reducing the risk of infection in healthcare is essential. The purpose of this study was to explore healthcare professionals’ experiences of awaiting a test result for a potential COVID-19 infection. Methods Qualitative interviews with 15 healthcare professionals were performed, underpinned by a phenomenological hermeneuti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 31 publications
(38 reference statements)
4
36
0
Order By: Relevance
“…If the participants knew their test result prior to the interview they were excluded. Furthermore, health professionals were excluded from this study as they were included in another study conducted by this research team [8]. Therefore, the first 15 participants who contacted the research team and didn't know their test result nor were working as health professionals were interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…If the participants knew their test result prior to the interview they were excluded. Furthermore, health professionals were excluded from this study as they were included in another study conducted by this research team [8]. Therefore, the first 15 participants who contacted the research team and didn't know their test result nor were working as health professionals were interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Despite descriptions of disrupted temporal structures regarding work schedules and work hours challenging the work life balance, a metaphor of being in war together highlighted cohesion and team spirit among HCPs. It has been reported that HCPs, despite experiencing strong pressure of fear of infection, exhaustion by heavy workloads and stress of caring for seriously ill COVID-19 patients still present a strong sense of duty and identity as a HCP (15,31). This dedication towards their work should, however, not overshadow and create imbalance regarding a HCPs' family life (27,32).…”
Section: Discussionmentioning
confidence: 99%
“…The ght against COVID-19 is, however, dependent on extraordinary efforts from, and collaboration between, various HCPs, e.g. nurses, doctors, physiotherapists, pharmacists and porters (15). They are currently facing frontline care and treatments for patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 has caused extensive societal, economic, and psychological impacts on humans within a disrupted environment. Additionally, how best t o support stressed and overworked medical staff (Missel, 2020) is a priority. Therefore, further actionable interventions that can establish a safe and secure lifestyle in the 'new normal' era are essential.…”
Section: Discussionmentioning
confidence: 99%